Exercise intolerance in HFpEF: arterial stiffness and abnormal left ventricular hemodynamic responses during exercise - Zern, Emily K. (J Card Fail, 2021)
BACKGROUND: Arterial stiffness is thought to contribute to the pathophysiology of heart failure with preserved ejection fraction (HFpEF). We sought to examine arterial stiffness in HFpEF and hypertension and investigate associations of arterial and left ventricular hemodynamic responses to exercise. METHODS: A total of 385 symptomatic individuals with EF ≥ 50% underwent upright cardiopulmonary exercise testing with invasive hemodynamic assessment of arterial stiffness and load (aortic augmentation pressure, augmentation index, systemic vascular resistance index, total arterial compliance index, effective arterial elastance index, and pulse pressure amplification) at rest and during incremental exercise. An abnormal hemodynamic response to exercise was defined as a steep increase in pulmonary capillary wedge pressure relative to cardiac output (ΔPCWP/ΔCO > 2 mmHg/L/min). We compared rest and exercise measures between HFpEF and hypertension in multivariable analyses. RESULTS: Among 188 HFpEF participants (age 61±13, 56% women), resting arterial stiffness parameters were worse compared to 94 hypertensive participants (age 55 ± 15, 52% women); these differences were accentuated during exercise in HFpEF (all p≤0.0001). Among all participants, exercise measures of arterial stiffness correlated with worse ΔPCWP/ΔCO. Specifically, a 1-SD higher exercise augmentation pressure was associated with 2.15-fold greater odds of abnormal LV hemodynamic response (95% CI 1.52–3.05, p<0.001). Further, exercise measures of systemic vascular resistance index, elastance index, and pulse pressure amplification correlated with lower peak VO(2). CONCLUSIONS: Exercise accentuates elevated arterial stiffness in HFpEF, which in turn correlate with left ventricular hemodynamic responses. Unfavorable ventricular-vascular interactions during exercise in HFpEF may contribute to exertional intolerance and inform future therapeutic interventions.